A third order correction to the Helmholtz equation - Jegorovs, J.; Mohring, J. (Mathematical Modelling and Analysis, 2005)
In this work we derive a third order correction to the classical Helmholtz equation. Starting from non‐linear Euler equations and using asymptotical analysis we get a decoupled system of linear, Helmholtz type equations, which are written in terms of the acoustical pressure functions. We present also a rather simple concept of the boundary conditions. Also numerical results and accompanying difficulties are discussed and presented.Helmholco lygties trečiosios eilės patikslinimasRemiantis Oilerio lygtimis ir asimptotine analize gautas Helmholco lygties trečiosios eilės patikslinimas. Akustiniam slėgiui gauta Helmholco tipo lygtis bei jai išvestos sąlygos. Pateikti skaitinio modeliavimo rezultatai.First Published Online: 14 Oct 2010